Docker Image Pipelines and Patterns - Kuenzli, Stephen (Manning Publications, 2020)
Stephen Kuenzli has designed, built, deployed, and operated highly available, scalable software systems for nearly 20 years. In this video, Stephen showcases how to build images automatically with Dockerfiles and patterns for tagging them.